RELATIONSHIP BETWEEN RELIGIOUS COPING AND SELF COMPETENCY ASSESSMENT WITH PARENTING STRESS IN PARENTS OF CHILDREN WITH SPECIAL NEEDS - Herlina Herlina; Ismawati Kosasih; Helli Ihsan; Tina Hayati Dahlan (PEDAGOGIA, 2022)
This study aims to determine the relationship between parents’ religious coping and perceived competencies in handling their children with special needs and their parental stress level. The subject of the study is 122 parents of children with an array of special needs, selected using an accidental sampling technique. Data for the study were obtained through the Indonesian version of Amer et al.’s BARCS questionnaires (2018), with some adaptations applied. Parents’ perception of their competence in handling their children with special needs was measured using the SEDKO-ABK questionnaire arranged by the researchers. At the same time, Berry Jones’s Parenting Stress Scale (1995) was adapted into the context of the parenting of children with special needs to measure parents’ stress levels. The data were processed using multiple regression statistical techniques on the significance level of α=0.05. Based on the result, it is discovered that 1) parents’ perception of their competence in handling their children with special needs affects their parental stress level, 2) the use of religious coping has an impact on parental stress level, and 3) self-perception on self-competence and the use of religious coping in handling children with special needs simultaneously give an impact on parental stress level.